Linking Data and Publications: Towards a Cross-Disciplinary Approach - Maarten Hoogerwerf; Mathias Lösch; Jochen Schirrwagen; Sarah Callaghan; Paolo Manghi; Katerina Iatropoulou; Dimitra Keramida; Najla Rettberg (International Journal of Digital Curation, 2013)
In this paper, we tackle the challenge of linking scholarly information in multi-disciplinary research infrastructures. There is a trend towards linking publications with research data and other information, but, as it is still emerging, this is handled differently by various initiatives and disciplines. For OpenAIRE, a European cross-disciplinary publication infrastructure, this poses the challenge of supporting these heterogeneous practices. Hence, OpenAIRE wants to contribute to the development of a common approach for discipline-independent linking practices between publications, data, project information and researchers. To this end, we constructed two demonstrators to identify commonalities and differences. The results show the importance of stable and unique identifiers, and support a ‘by reference’ approach of interlinking research results. This approach allows discipline-specific research information to be managed independently in distributed systems and avoids redundant maintenance. Furthermore, it allows these disciplinary systems to manage the specialized structures of their contents themselves.